Genome-wide identification and characterization of OVATE family proteins in Betula luminifera reveals involvement of BlOFP3 and BlOFP5 genes in leaf development - Borah, Priyanka; Ni, Fei; Ying, Weiyang; Zhuang, Hebi; Chong, Sun-Li; Hu, Xian-Ge; Yang, Jun; Lin, Er-pei; Huang, Huahong (Frontiers in Plant Science, 2022)
Ovate family proteins (OFP) are plant-specific transcription factors involved in regulating morphologies of the lateral organs, plant growth and development. However, the functional roles of OFP genes in Betula luminifera, an important timber tree species, are not well studied. In this study, we identified 20 BlOFP genes and analyzed their phylogenetic relationship, gene structure, conserved motifs, and cis-elements. Further, expression analysis indicates that BlOFP genes were up-regulated in leaves on the one-year-old branch compared to leaves on the current-year branch and bract, except BlOFP7, BlOFP11, BlOFP14 and BlOFP12. The overexpression of BlOFP3 and BlOFP5 in Arabidopsis thaliana not only resulted in a slower growth rate but also produced sawtooth shape, flatter and darker green rosette leaves. Further investigation showed that the leaf thickness of the transgenic plants was more than double that of the wild type, which was caused by the increasement in the number and size of palisade tissue cells. Furthermore, the expression analysis also indicated that the expressions of several genes related to leaf development were significantly changed in the transgene plants. These results suggested the significant roles of BlOFP3 and BlOFP5 in leaf development. Moreover, protein-protein interaction studies showed that BlOFP3 interacts with BlKNAT5, and BlOFP5 interacts with BlKNAT5, BlBLH6 and BlBLH7. In conclusion, our study demonstrates that BlOFP3 and BlOFP5 were involved in leaf shape and thickness regulation by forming a complex with BlKNAT5, BlBLH6 and BlBLH7. In addition, our study serves as a guide for future functional genomic studies of OFP genes of the B. luminifera.